2007
DOI: 10.1111/j.1745-6584.2006.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat, Chloride, and Specific Conductance as Ground Water Tracers near Streams

Abstract: Commonly measured water quality parameters were compared to heat as tracers of stream water exchange with ground water. Temperature, specific conductance, and chloride were sampled at various frequencies in the stream and adjacent wells over a 2-year period. Strong seasonal variations in stream water were observed for temperature and specific conductance. In observation wells where the temperature response correlated to stream water, chloride and specific conductance values were similar to stream water values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 23 publications
1
55
1
Order By: Relevance
“…Furthermore, by conducting the study on two rivers in the same catchment, controls on the gaining and losing behaviour of neighbouring rivers can be investigated. Studies that employ multiple techniques for such investigations have been historically less common than research focussed on one or two methods, and can provide additional and more robust information for groundwater-surface water studies (Cox et al, 2007).…”
Section: N P Unland Et Al: Investigating the Spatio-temporal Variamentioning
confidence: 99%
“…Furthermore, by conducting the study on two rivers in the same catchment, controls on the gaining and losing behaviour of neighbouring rivers can be investigated. Studies that employ multiple techniques for such investigations have been historically less common than research focussed on one or two methods, and can provide additional and more robust information for groundwater-surface water studies (Cox et al, 2007).…”
Section: N P Unland Et Al: Investigating the Spatio-temporal Variamentioning
confidence: 99%
“…While multi-method approaches have historically been less common, they can overcome the large uncertainties that are attributed to single method applications and provide additional and more robust information for example in groundwater-surface water interactions [3][4][5] to obtain unequivocal results [6]. Moreover, by combining methods in different compartments of the hydrological cycle or different scales within the catchment (plot-, reach-scale) long time series are not necessarily needed to understand catchment reaction or the contribution of runoff components during varying saturation conditions (floods or low flow) in small and meso-scale catchments [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Universally heterogeneity in streambed hydraulic conductivities leads to streambed exchanges in all three orientations, plan view [e.g., Conant, 2004], cross section, and longitudinal to stream [e.g., Becker et al, 2004;Essaid et al, 2006]. For significant hydraulic gradients, Su et al [2004] portrayed the influence of variable hydraulic conductivities on the complexity of streambed flow patterns, and Cox et al [2007] showed the impacts of gradual downstream changes in both hydraulic gradients and hydraulic conductivities on crosssection streambed exchange patterns. On a larger spatial scale, combined seasonal variability in near-stream and regional groundwater flow patterns combined with reach-specific streambed geomorphology has been shown to result in both spatial and temporal variability in streambed exchanges along tributary streams [e.g., Niswonger and Prudic, 2003;Stonestrom et al, 2007].…”
Section: Research On Streambed Exchange Patternsmentioning
confidence: 99%